Pengaruh Tingkat Kecemasan dan Performa Atlet Cabang Olahraga Bola Tangan (handball) Universitas Singaperbangsa Karawang - Nurhadi, Maha Dewi Afifah; Sembiring, Dian Agnesa; Dewi, R. Retna Kinanti (Jurnal Keolahragaan, 2023)
This research is a type of quantitative descriptive data survey research that aims to analyze the effect of anxiety levels on handball athletes at Singaperbangsa University in Karawang. The research method used is data collection filling out questionnaires to 10 handball athletes, of which 80% are male athletes and 20% are female athletes. The age of respondents was mostly the adult group (20-27 years) as much as 60% and the youth group (15-19 years) as much as 40%. Data collection is done through Google Form which consists of 26 statements using a Likert scale. The survey research results of the processed questionnaire data show the average value is 80.50 with a significant normality test of 0.996. The results measured in this study have been tested for validity and reliability has been confirmed previously. The conclusion from handball is that sport psychology has a very important role in understanding and managing athletes' anxiety. This anxiety can arise from match pressure, performance anxiety, and psychological factors that can affect athletes. However, by using sport psychology approaches, including mental training, support from teammates, and emotional management, athletes have the ability to overcome such anxiety. Therefore, controlling anxiety in sport is not impossible, and athletes can optimize their performance.